Immunomodulatory Effects of Dopamine in Inflammatory Diseases - Feng, Yifei; Lu, Yan (Frontiers in Immunology, 2021)
Dopamine (DA) receptor, a significant G protein-coupled receptor, is classified into two families: D1-like (D1 and D5) and D2-like (D2, D3, and D4) receptor families, with further formation of homodimers, heteromers, and receptor mosaic. Increasing evidence suggests that the immune system can be affected by the nervous system and neurotransmitters, such as dopamine. Recently, the role of the DA receptor in inflammation has been widely studied, mainly focusing on NLRP3 inflammasome, NF-κB pathway, and immune cells. This article provides a brief review of the structures, functions, and signaling pathways of DA receptors and their relationships with inflammation. With detailed descriptions of their roles in Parkinson disease, inflammatory bowel disease, rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis, this article provides a theoretical basis for drug development targeting DA receptors in inflammatory diseases.